Characterizing the conductivity of ICA joints by the mean intercept length of Ag flakes. Issue 1 (1st February 2016) - Illés, Balázs; Krammer, Olivér; Géczy, Attila; Garami, Tamás
Abstract : Purpose: – The purpose of this paper is to present a novel and alternative method for the characterization of isotropic conductive adhesive (ICA) joints' conductivity by the calculation of the mean intercept length of conductive flakes in the cured joint. ICAs are widely used in the field of hybrid electronics or special printed circuit board applications, such as temperature sensitive or flexible circuits. The main quality parameters of the ICA joints are the conductivity and the mechanical strength. Design/methodology/approach: – For the experiments, one-component Ag-filled thermoset ICA paste was used on FR4 printed circuit test board to join zero-ohm resistors. Six different curing temperatures were applied: 120, 150, 175, 210, 230 and 250°C. The conductivity of the joints was measured in situ during the curing process. Micrographs were taken from the cross-sectioned joints, and the mean intercept length was calculated on them after image processing steps. Findings: – Results of the measured conductivity and the mean intercept length were compared, and acceptable correlation was found for what can be used for characterizing the conductibility of ICA joints. Research limitations/implications: – Investigating and characterizing the conductivity of ICA joints by an image processing method. Originality/value: – The main advantage of this method compared to the electrical measurements is that the conductivity characterization is possible on any kind of component. Therefore, this method can be used in any appliances not only in test circuits.